2014
DOI: 10.3856/vol42-issue3-fulltext-12
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake efficiency of Gracilaria chilensis and Ulva lactuca in an IMTA system with the red abalone Haliotis rufescens

Abstract: ABSTRACT. The current study examined the nutrient uptake efficiency of Ulva lactuca and Gracilaria chilensis cultivated in tanks associated with the wastewater of a land-based abalone culture. The experiments evaluated different seaweed stocking densities (1200, 1900, 2600, and 3200 g m -2 ) and water exchange rates (60, 80, 125, and 250 L h -1 ). The results show that both U. lactuca and G. chilensis were efficient in capturing and removing all of the inorganic nutrients originating from the abalone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
(46 reference statements)
4
18
0
1
Order By: Relevance
“…Our experiments were planned to be repeated twice to address the effect of seasonality on the seaweeds' performance. It should be noted that both U. rigida and G. conferta displayed higher SGRs in dependency to preferred environmental conditions such as light and temperature, similar to previous studies (Friedlander et al 1987;Macchiavello & Bulboa 2014). In the present study, the optimal temperatures and irradiance for Figure 7 Average total ammonia nitrogen uptake rates (g m À2 day À1 ) of the different seaweed pairings.…”
Section: Discussionsupporting
confidence: 86%
“…Our experiments were planned to be repeated twice to address the effect of seasonality on the seaweeds' performance. It should be noted that both U. rigida and G. conferta displayed higher SGRs in dependency to preferred environmental conditions such as light and temperature, similar to previous studies (Friedlander et al 1987;Macchiavello & Bulboa 2014). In the present study, the optimal temperatures and irradiance for Figure 7 Average total ammonia nitrogen uptake rates (g m À2 day À1 ) of the different seaweed pairings.…”
Section: Discussionsupporting
confidence: 86%
“…In the application of macroalgae for bioremediation, the optimum macroalgal density is a main factor that should be used by farmers to obtain effective results [20,23]. The nonlinear effect found of macroalgal density on NUE (except NH 3 ) by C. lentillifera in our study (Table 4) confirms a previous study by Macchiavello and Bulboa [28]. The linear effect on NH 3 might have been due to the passive diffusion of NH 3 [14].…”
Section: Discussionsupporting
confidence: 85%
“…Of these, macroalgal density, salinity, and aeration can be controlled at farm levels depending on objectives of the aquaculture management [16,20,23]. As a decline in nutrient uptake and macroalgal growth occurs when macroalgal density and salinity are too high or too low [16,[24][25][26][27][28], it indicates the non-linear effects of these factors on nutrient uptake. Therefore, it is critical to determine the optimum levels of macroalgal density and salinity for the effective applications of macroalgae for aquaculture effluent treatment [16,18,20,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The higher levels of protein content observed in Ulva growing on co-culture systems with abalone, either in the cage culture or in the land-based recirculating aqua culture system (RAS), would be related to its production under high nitrogen culture condition than those collected from nature where seawater contain low nutrient concentrations. Ulva has a good capability for removing nutrients, particularly nitrogen and phosphate from animal effluents (Robertson-Andersson et al, 2008;Macchiavello and Bulboa, 2014). Previous studies reported that Ulva can assimilate as much as 100% for NH 4 + and at least 80%…”
Section: Protein Contentmentioning
confidence: 99%
“…for NO 3 generated by abalone aquaculture (Macchiavello and Bulboa, 2014;Robertson and Andersson et al, 2008) and these nitrogen compounds increase protein and pigment content of the algae (Viera et al, 2005;Figueroa et al, 2009). Also, Ulva under culture, either in cage or in recirculating aqua culture system, that receives effluent from cultured animals (fish, crustacean or molluscs), benefit not only from a rich source of ammonia but also from an important and free source of dissolved inorganic C coming from animals respiration that becomes available for algal photosynthesis (Figueroa et al, 2009).…”
Section: Protein Contentmentioning
confidence: 99%